IMPROVED TRANSLATION AND UNDERSTANDING ABILITY AL-QUR'AN IN CHILDREN USING THE AN-NASHR METHOD - Salamah, Umi; Ubaidillah, Ibnu (MUADDIB Jurnal Kependidikan dan Keislaman, 2023)
Al-Qur'an education includes important aspects including tartil, writing, memorizing, translating, and understanding and practicing it in everyday life. This research aims to describe and analyze the increase in children's ability to translate and understand the Al-Qur'an using the An-Nashr method. The research uses a qualitative case study approach with data collection carried out through interviews, observation, documentation studies and triangulation. Data analysis uses the Miles, Huberman, and Saldana interactive model which includes data condensation, data display, and drawing conclusions. The research results show that the implementation of the An-Nashr method is carried out through three stages: planning, implementation and evaluation. The implication of applying the An-Nashr method is to increase the ability to translate and understand the Al-Qur'an through aspects of understanding which include interpretation per word or per verse, asbabun nuzul, types of letters (makkiyyah & madaniyyah), content of letters, nahwu, and shorof; It is easier for students to learn the Koran because it is taught directly through memorizing translations without needing a dictionary or studying Arabic grammar first.